Pravna priroda prometnih znakova na cestama - Inić, Milan (Promet - Traffic&Transportation, 2012)
Traffic signs refer to a specific technique of controlling some human relations, conditions and behavior in traffic. In other spheres of community life, as to a degree in traffic, these relationships, conditions and behavior patterns are being regulated by legal rules (standards) being communicated descriptively. Therefore it is important to define the legal nature of traffic signs, their impacts as referring to the obligations and liabilities, as well as the differences and specific aspects with reference to traditional conventional legal rules and standards.